استدعاءُ المقدَّسِ الدينيِ في شِعرِ عارفِ الساعدي - حسين علي الموسوي عزيز (Journal of College of Education, 2020)
This is a research, which deals with Aref Al-Saadi’s poetry, whose title is (Summoning the Religious Sacred in Aref Al-Saadi’s Poetry). It is an approximation to the mode of the religious sacred in his poetry in which the researcher examines the summoning of the religious sacred in Aref Al-Saadi’s entire poetic collections, in his poetic works and his book (The last Adam). The researcher divides the study into three fields; the direction of summoning the personality in Al-Saadi’s poetry, the mechanisms of summoning the religious sacred, from intertextuality and the semantics of the title, the narrative structure, the symbol, and the functions of summoning the religious sacred, from mysticism and existentialism, etc. It brings him closer to the human being, brings him down from his transcendence and metaphysics, makes him in an earthly way, converses with him about human crises and those concerns, and express them through him